Adolescent health outcomes: associations with child maltreatment and peer victimization - Samantha Salmon; Isabel Garcés Dávila; Tamara L. Taillieu; Ashley Stewart-Tufescu; Laura Duncan; Janique Fortier; Shannon Struck; Katholiki Georgiades; Harriet L. MacMillan; Melissa Kimber; Andrea Gonzalez; Tracie O. Afifi (BMC, 2022)
Abstract Background Child maltreatment (CM) and peer victimization (PV) are serious issues affecting children and adolescents. Despite the interrelatedness of these exposures, few studies have investigated their co-occurrence and combined impact on health outcomes. The study objectives were to determine the overall and sex-specific prevalence of lifetime exposure to CM and past-month exposure to PV in adolescents, and the impact of CM and PV co-occurrence on non-suicidal self-injury, suicidality, mental health disorders, and physical health conditions. Methods Adolescents aged 14-17 years (n = 2,910) from the 2014 Ontario Child Health Study were included. CM included physical, sexual, and emotional abuse, physical neglect, and exposure to intimate partner violence. PV included school-based, cyber, and discriminatory victimization. Logistic regression was used to compare prevalence by sex, examine independent associations and interaction effects in sex-stratified models and in the entire sample, and cumulative effects in the entire sample. Results About 10% of the sample reported exposure to both CM and PV. Sex differences were as follows: females had increased odds of CM, self-injury, suicidality, and internalizing disorders, and males had greater odds of PV, externalizing disorders, and physical health conditions. Significant cumulative and interaction effects were found in the entire sample and interaction effects were found in sex-stratified models, indicating that the presence of both CM and PV magnifies the effect on self-injury and all suicide outcomes for females, and on suicidal ideation, suicide attempts, and mental health disorders for males. Conclusions Experiencing both CM and PV substantially increases the odds of poor health outcomes among adolescents, and moderating relationships affect females and males differently. Continued research is needed to develop effective prevention strategies and to examine protective factors that may mitigate these adverse health outcomes, including potential sex differences.